Drag force acting on biofouled net panels - Swift, M. Robinson; Fredriksson, David W.; Unrein, Alexander; Fullerton, Brett; Patursson, Oystein; Baldwin, Kenneth (Aquacultural engineering, 2006)
Measurements were made to assess the increase in drag on aquaculture cage netting due to biofouling. Drag force was obtained by towing net panels, perpendicular to the incident flow, in experiments conducted in a tow tank and in the field. The net panels were fabricated from netting stretched within a 1 m 2 pipe frame. They were towed at various speeds, and drag force was measured using a bridle-pulley arrangement terminating in a load cell. The frame without netting was also drag tested so that net-only results could be obtained by subtracting out the frame contribution. Measurements of drag force and velocity were processed to yield drag coefficients. Clean nets were drag tested in the University of New Hampshire (UNH) 36.5 m long tow tank. Nets were then exposed to biofouling during the summer of 2004 at the UNH open ocean aquaculture demonstration site 1.6 km south of the Isles of Shoals, New Hampshire, U.S.A. Nine net panels were recovered on 6 October 2004 and immediately drag tested at sea to minimize disturbing the fouling communities. The majority of the growth was skeleton shrimp ( Caprella sp.) with some colonial hydroids ( Tubularia sp.), blue mussels ( Mytilus edulus) and rock borer clams ( Hiatella actica). Since the deployment depth was 15 m (commensurate with submerged cages at the site), no algae were present. The net panels had been subject to several different antifouling treatments, so the extent of growth varied amongst the panels. Drag force measurements were made using a bridle-pulley-load cell configuration similar to that employed in the tow tank. Fixtures and instruments were mounted on an unpowered catamaran that was towed alongside a workboat. Thus, the catamaran served as the “carriage” for field measurements. Increases in net-only drag coefficient varied from 6 to 240% of the clean net values. The maximum biofouled net drag coefficient was 0.599 based on net outline area. Biofouled drag coefficients generally increased with solidity (projected area of blockage divided by outline area) and volume of growth. There was, however, considerable scatter attributed in part to different mixes of species present.